The relationship between nutritional status and the prognosis of COVID-19: A retrospective analysis of 63 patients. Issue 14 (9th April 2021) - Li, Yuhong; Tong, Shijun; Hu, Xueyuan; Wang, Yuanjun; Lv, Ronghua; Ai, Shaozheng; Hou, Ming; Fan, Haining; Shen, Youlu
Abstract : Abstract: It is important for patients to maintain a good nutritional status as a health promotion strategy to improve the immune function and thus the prognosis of coronavirus disease 2019 (COVID-19). The objective of this retrospective study is to analyze the relationships of nutritional status with inflammation levels, protein reserves, baseline immune status, severity, length of hospital stay, and prognosis of COVID-19 patients. A total of 63 COVID-19 patients hospitalized in the People's Hospital and the Traditional Chinese Medicine Hospital of the Xinzhou District, Wuhan, China, from January 29, 2020 to March 17, 2020. Sixty-three patients were divided into 3 groups according to the guidelines, moderate (n = 22), severe (n = 14), and critical (n = 25), respectively. The differences in the total nutrition risk screening (NRS) score, inflammation level, protein reserve, baseline immune status, length of hospital stay, and prognosis were compared among patients with moderate, severe, and critical COVID-19. Patients with higher NRS scores tend to have more severe COVID-19, higher C-reactive protein and serum procalcitonin levels, higher white blood cell counts, lower lymphocyte counts, and higher mortality rates ( P  < .05). Nutritional status may be an indirect factor of the severity and prognosis of COVID-19.